PENTINGNYA PENANGANAN PASCABENCANA YANG BERFOKUS PADA PENDUDUK UNTUK MEWUJUDKAN BUILD BACK BETTER: PEMBELAJARAN DARI BENCANA PALU, SIGI, DAN DONGGALA - Gusti Ayu Ketut Surtiari (Research Centre for Population, Indonesian Institute of Sciences, 2019)
Sendai Framework 2015-2030 highlights the importance of build back better after a disaster. Post-disaster management is an important stage to reach this goal.Â In general, rehabilitation process tends to focus on physical aspects and rarely considering people as the center. This paper aims to examine the rehabilitation process after earthquake and tsunami in Central Sulawesi in 2018 focused on opportunities and challenges to build back better. The temporary shelter (Huntara) is selected as the case study as it is the most urgent need after disaster. Data analysis is based on literature reviews and primary data from rapid assessment in December 2018 in Palu, Sigi, and Donggala. Based on the people-centered concept, results show that most of the temporary shelters are provided as a product and less concern about its function as a process. However, some temporary shelters have considered the process that comes from civil societyâ€™s initiatives. They propose Huntara as a transition by proposing a feeling of comfort and secure. To conclude, survivors need to be involved in the rehabilitation process to build back better.